N-(4-Chlorophenyl)-2-nitrobenzenesulfonamide - Chaithanya, U. (International Union of Crystallography, 2012)
In the title compound, C(12)H(9)ClN(2)O(4)S, the dihedral angle between the aromatic rings is 70.27 (8)°. In the crystal, molecules are linked by pairs of N—H⋯O(S) hydrogen bonds, forming inversion dimers.